Binding of Ferric Enterobactin by the Escherichia coli Periplasmic Protein FepB - Sprencel, Cathy (American Society for Microbiology, 2000)
The periplasmic protein FepB of Escherichia coli is a component of the ferric enterobactin transport system. We overexpressed and purified the binding protein 23-fold from periplasmic extracts by ammonium sulfate precipitation and chromatographic methods, with a yield of 20%, to a final specific activity of 15,500 pmol of ferric enterobactin bound/mg. Periplasmic fluid from cells overexpressing the binding protein adsorbed catecholate ferric siderophores with high affinity: in a gel filtration chromatography assay the K(d) of the ferric enterobactin-FepB binding reaction was approximately 135 nM. Intrinsic fluorescence measurements of binding by the purified protein, which were more accurate, showed higher affinity for both ferric enterobactin (K(d) = 30 nM) and ferric enantioenterobactin (K(d) = 15 nM), the left-handed stereoisomer of the natural E. coli siderophore. Purified FepB also adsorbed the apo-siderophore, enterobactin, with comparable affinity (K(d) = 60 nM) but did not bind ferric agrobactin. Polyclonal rabbit antisera and mouse monoclonal antibodies raised against nearly homogeneous preparations of FepB specifically recognized it in solid-phase immunoassays. These sera enabled the measurement of the FepB concentration in vivo when expressed from the chromosome (4,000 copies/cell) or from multicopy plasmids (>100,000 copies/cell). Overexpression of the binding protein did not enhance the overall affinity or rate of ferric enterobactin transport, supporting the conclusion that the rate-limiting step of ferric siderophore uptake through the cell envelope is passage through the outer membrane.